2011
DOI: 10.1002/14651858.cd007559.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mind-body interventions during pregnancy for preventing or treating women's anxiety

Abstract: Mind-body interventions might benefit women's anxiety during pregnancy. Based on individual studies, there is some but no strong evidence for the effectiveness of mind-body interventions for the management of anxiety during pregnancy. The main limitations of the studies were the lack of blinding and insufficient details on the methods used for randomization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 99 publications
3
63
0
14
Order By: Relevance
“…In a Cochrane review, Hunot, Churchill, Silva de Lima, and Teixeira (2007) concluded that CBT was more effective than treatment as usual or wait list in achieving a clinically significant reduction in generalised anxiety and worry (RR 0.64, 95% CI 0.55-0.74). A Cochrane review of mind -body techniques showed an emerging body of evidence for their effectiveness for reducing anxiety in women who are pregnant or have just given birth (Marc et al, 2011). There is increasing evidence for the effectiveness of CBT and mindfulness when used in combination (Sipe & Eisendrath, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In a Cochrane review, Hunot, Churchill, Silva de Lima, and Teixeira (2007) concluded that CBT was more effective than treatment as usual or wait list in achieving a clinically significant reduction in generalised anxiety and worry (RR 0.64, 95% CI 0.55-0.74). A Cochrane review of mind -body techniques showed an emerging body of evidence for their effectiveness for reducing anxiety in women who are pregnant or have just given birth (Marc et al, 2011). There is increasing evidence for the effectiveness of CBT and mindfulness when used in combination (Sipe & Eisendrath, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…No harmful effects have been linked to mind-body CAM interventions, such as yoga, hypnotherapy, and imagery [9]. However, the effects of herbal preparations during pregnancy have not been well measured and have been linked to adverse events [10].…”
Section: Discussionmentioning
confidence: 99%
“…For example, no harmful effects have been linked to Mind-body CAM interventions, such as yoga, hypnotherapy, and imagery [9], and it would be unlikely to encounter an adverse effect from prayer or energy healing when used in concert with conventional medicine. However, for Alternative Medicine practices, Biologic-based therapies, and Manipulative and Body-based methods, the risk versus benefit calculation is less straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…The growing acceptability of CAM therapies by HCPs and pregnant women in treating physical-health concerns may provide a pathway through which women with subthreshold mood symptoms engage with treatment without threat of stigma. However, midwives' and obstetricians' knowledge and understanding of the possible risks to women is limited by the public's enthusiasm for CAM exceeding the scientific evidence base for their use (Marc et al, 2011).…”
Section: Which Pregnant Women May Benefit From Cam?mentioning
confidence: 99%
“…Systematic reviews frequently report a paucity of randomised controlled trials (RCTs) of CAMs in pregnancy, and studies often suffer from poor methodological quality (Marc et al, 2011). This is often not at the fault of the researcher, but there are inherent difficulties in conducting RCTs of CAMs which include an inability to effectively blind participants, to maintain treatment fidelity and to select suitable comparison groups.…”
Section: Issues Of Testing Cam Therapiesmentioning
confidence: 99%